(untitled) (Advancements in Homeopathic Research, 2025)
A complex inflammatory illness of the nasal and paranasal mucosae, chronic rhinosinusitis (CRS) manifests itself in a multitude of symptom combinations. Conditions ranging from unilateral single sinus disease to extensive sinonasal airway inflammation can be classified as chronic rhinosinusitis. Allopathic medicines are frequently used to treat acute attack symptoms. Allopathic medication for sinusitis, however, can be hazardous if used repeatedly or over an extended period of time and does not prevent further infections. Long term sinus infections have been shown to respond effectively to homoeopathy since the patient is treated individually in this method.